2005
DOI: 10.1021/la047217h
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Capsule Catalyst and Its Application for Direct Synthesis of Middle Isoparaffins

Abstract: A catalyst in the form of a capsule catalyst was prepared by coating HZSM5 membrane on a preshaped Co/SiO2 catalyst pellet. The capsule catalyst with HZSM5 membrane exhibited excellent selectivity for light hydrocarbon synthesis, especially for isoparaffin synthesis from syngas (CO + H2). Long-chain hydrocarbon formation was totally suppressed by the zeolite membrane. The modification of membrane and core catalyst significantly improved the catalytic properties of these new kinds of capsule catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 12 publications
0
91
0
Order By: Relevance
“…This confined structure enabled cobalt catalyst showing special catalytic performances and product distribution in F-T synthesis. For example, Tsubaki co workers [6][7][8][9] had prepared core@shell cobalt catalysts by coating H-ZSM-5 zeolite membranes on the Co/SiO 2 catalysts, which showed an excellent selectivity to the C 5 -C 11 isoparaffins (gasoline distillates) benefiting from the confined reaction conditions constructed by H-ZSM-5 membranes. Moreover, the article of Trépanier et al [10] has also showed that carbon nanotubes, when used as a cobalt catalyst support, allowed a better Co dispersion and minimized the Co metal phase interaction with the support.…”
Section: Introductionmentioning
confidence: 99%
“…This confined structure enabled cobalt catalyst showing special catalytic performances and product distribution in F-T synthesis. For example, Tsubaki co workers [6][7][8][9] had prepared core@shell cobalt catalysts by coating H-ZSM-5 zeolite membranes on the Co/SiO 2 catalysts, which showed an excellent selectivity to the C 5 -C 11 isoparaffins (gasoline distillates) benefiting from the confined reaction conditions constructed by H-ZSM-5 membranes. Moreover, the article of Trépanier et al [10] has also showed that carbon nanotubes, when used as a cobalt catalyst support, allowed a better Co dispersion and minimized the Co metal phase interaction with the support.…”
Section: Introductionmentioning
confidence: 99%
“…The i-paraffin selectivity of 29.8% being higher than that of Fe/SiO2 catalyst (12.9%) and the physical mixture (16.6%) was attributed to the combination of the hydrogenation and isomerization of the formed olefins at the core and the hydrocracking and isomerization of the heavy hydrocarbons in the dual-membrane catalyst. Moreover, relatively low methane selectivity (14.9%) compared to the other reported core-shell catalysts was obtained [234,256,281], indeed being still higher than that of the core catalyst and the physical mixture. Additionally, Yang et al reported the benefit of controlling the pellet size for the preparation of H-ZSM-5 zeolite capsule catalysts on small Ru/SiO2 pellets [255].…”
Section: Application As Catalytic Membranesmentioning
confidence: 66%
“…Accordingly, the selectivity could be significantly improved since the intermediate products are enforced to pass a zeolite membrane in order to desorb from the Fischer-Tropsch catalyst experiencing a higher possibility for further conversion so as to yield the desired product. In detail, the working group of Tsubaki [234,253,254] coated H-ZSM-5 membranes on preshaped Co/SiO2 pellets and evaluated their performances in i-paraffins synthesis from syngas. Thereby, syngas permeated through the membrane to the core catalyst and reacted to straight-chain hydrocarbons which were then hydrocracked and isomerized while passing the zeolite channels as show schematically in Figure 12.…”
Section: Application As Catalytic Membranesmentioning
confidence: 99%
“…Some researchers have investigated the hybrid or composite systems consisting of cobalt component as the FTS catalyst and zeolite as the cracking catalyst by using the following representative methods; (i) cobalt-based catalyst mixed physically with zeolites [5][6][7], (ii) zeolite supported cobalt-based hybrid catalyst prepared by wet-impregnation method [8], (iii) membrane-coating using zeolite component on the supported Co/SiO2 catalyst [9][10][11][12], and (iv) cobalt-based hybrid catalyst co-precipitated in a slurry of zeolite [13]. However, the enhancement of Co reducibility on Pt as a promoter has been reported for several supports (e.g.…”
Section: Introductionmentioning
confidence: 99%